Commodification of Art: Old and New Research Perspectives - ФархатдиновНаиль Галимханович (Journal of Economic Sociology, 2011)
The author makes an attempt to codify the old and the new research perspectives in the sociology of art markets. He describes research approaches developed in the frameworks of the cultural production paradigm which considers the market as an institution contributing to cultural products circulation. Market structure and prices on the pieces of art are the key issues here. Recently the new approaches emerged with a special focus on a role of emotions in the markets of art and ritual nature of relations. Finally, an alternative anthropological approach to the analysis of commodification of art is proposed.